Dissipative Hamiltonian realisation and robust H∞ control of induction motor considering iron losses for electric vehicles. (1st January 2013) - Pei, Wenhui; Zhang, Chenghui; Cui, Naxin; Li, Ke
The dissipative Hamiltonian realisation and robust H ∞ control of induction motor considering iron losses for electric vehicle are investigated in this paper. First, the dissipative Hamiltonian of the electric vehicle drive system is obtained based on the system's mathematical model in a synchronously rotating frame. Then, a robust co-ordinated tracking controller is designed based on the dissipative Hamiltonian form. One part of the controller is designed by using the method of interconnection and damping assignment to ensure the system's stability, and another part is designed by using the Hamiltonian system's robust H ∞ technique to attenuate external disturbances. The simulation results show that the controller proposed in the paper works very well in robust tracking of induction motor.